Math(Please help)
posted by Hannah .
For f(x) = 2x3 and g(x)= 2x^2 find,
a) (f + g)(x) = My answer is
2x^2 + 2x  3. Is this correct?
b) (f  g)(x) How would you do this?
c) (f X g)(2) I do not know what to do since the 2 is there.

Sorry I wanted to add something else!
Determine whether the graph of the following equation is symmetric with respect to the xaxis, the yaxis, and the origin.
y^2  x  49 = 0
For x axis y^2  x  9 = 0 is not the same as the first equation so it is not symmetrical to the xaxis. Correct?
For the yaxis y^2 + x  49 = 0 is not the same as the first equation so it is not symmetrical to the yaxis. Correct?
For the origin y^2 + x  49 = 0 is not the same as the first equation so itis not symmetrical to the origin either. Am I correct? 
a. (f + g)(x) = f(x) + g(x) =(2x  3 +
2x^2.
b. (f  g)(x) = f(x)  g(x) = (2x 3)
 2x^2.
c. (f * g)(x) = f(x) * g(x) = (2x 3)
* 2x^2 = 4x^3  6x^2.
y^2  x  49 = 0.
Solve for x:
x = y^2  49 = 0,
This x parabola is the difference of 2 squares:
(y + 7) (y  7) = 0,
y + 7 = 0,
y = 7,
y  7 = 0,
y = 7.
Axis of symmetry: y = (7+7)/2 = 0,
y = 0 is a hor line which lies on the x axis. 
c. (f.g)(2) = f(2) * g(2) = (2*23) *
(2 * 2^2) = 1 * 8 = 8.